RANCANGAN BAHAN AJAR PENYELESAIAN RANGKAIAN LISTRIK 2 & 3 LOOP MENGGUNAKAN METODE ELIMINASI GAUSS-JORDAN - Ni'mah, Sima; Lailatul Nuraini (Journal of Teaching and Learning Physics, 2025)
This research aims to teaching materials for solving 2 and 3 loop electrical circuits using the Gauss-Jordan elimination method as an innovative alternative in physics learning. The research method used is non-experimental research with a quantitative descriptive approach. Literature studies were conducted to analyse the theory of simple n-loop electrical circuits and develop new solutions using the Gauss-Jordan elimination method. The design of teaching materials that had been made was then validated by 2 expert validators and 3 user validators. The validation results showed that the designed teaching materials received an average score of 4.53 with a percentage of 90.6% from expert validators, as well as an average score of 4.34 with a percentage of 86.6% from user validators, both with very valid criteria. The overall average validation percentage of 88.6% indicates that this teaching material is suitable for use in physics learning activities.